Immunohistochemical and morphometrical evaluation of well-differentiated thyroid tumor of uncertain malignant potential - Mohamed, Dareen; Shamlola, Maha (Indian journal of pathology & microbiology, 2019)
Context: Well-differentiated tumor of uncertain malignant potential (WDT-UMP) were encapsulated follicular pattern tumors with diffuse equivocal or focal unequivocal papillary thyroid carcinoma (PTC) type nuclear changes without definite invasion. These tumors are suggested to be borderline in its nature. Immunohistochemistry by CD56, P63, and CK19 are common markers used in differentiation between benign and malignant thyroid tumor. Computerized nuclear morphometry is an inexpensive objective and reproducible tool to evaluate histological features of thyroid tumors. Aims: To categorize WDT-UMP using combined nuclear morphometry and immunohistochemistry of CD56, P63, and CK19. Subjects and Methods: We used CD56, P63, and CK19 immunostaining and mean nuclear area and perimeter morphometry on 20 cases of WDT-UMP, 25 cases malignant thyroid tumors, and 25 cases benign thyroid lesions. Statistical Analysis Used: Student's t-test (Unpaired), analysis of variance (ANOVA) test, and Chi-square tests by SPSS V. 20. Results: Significant differences were obtained between WDT-UMP and benign group according to the three markers, but no significant difference between WDT-UMP and malignant group. The mean nuclear area and mean nuclear perimeter were significantly higher in WDT-UMP group in comparison with the benign group while there were no significant differences with the malignant group. Conclusion: WDT-UMP are intermediate lesions differing from benign lesions of the thyroid and sharing some criteria with PTC to a certain extent.